2002
DOI: 10.1038/sj.jhh.1001434
|View full text |Cite
|
Sign up to set email alerts
|

AT1-receptor blockers: differences that matter

Abstract: The available angiotensin II type 1 (AT 1 )-receptor blockers differ markedly in their pharmacological properties and clinical efficacy. Losartan shifts the dose-response curve for angiotensin II to the right without affecting the maximal response; this antagonism can be overcome by increasing concentrations of angiotensin II and thus losartan acts as a surmountable antagonist. By contrast, other agents suppress the maximal response to angiotensin II to varying extents; this can not be overcome by increasing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 31 publications
2
19
1
Order By: Relevance
“…It confirms our previous report where we demonstrated that perindopril decreased PAI-1 compared to losartan, in hypertensive, type II diabetic patients. 6 Finally, as expected, 4,6 AER was decreased at the end of the study in both groups (À47.1 and À44.5%, respectively). Our patients started as normoalbuminuric and remained normoalbuminuric for all the phases of the study, probably because the glycaemic control was good and the antihypertensive therapy stopped the possible progression to microalbuminuria.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…It confirms our previous report where we demonstrated that perindopril decreased PAI-1 compared to losartan, in hypertensive, type II diabetic patients. 6 Finally, as expected, 4,6 AER was decreased at the end of the study in both groups (À47.1 and À44.5%, respectively). Our patients started as normoalbuminuric and remained normoalbuminuric for all the phases of the study, probably because the glycaemic control was good and the antihypertensive therapy stopped the possible progression to microalbuminuria.…”
supporting
confidence: 81%
“…3 Metabolic abnormalities as insulin resistance, impairment lipid profile, and decreased fibrinolytic activity can be improved by ACE inhibitors. 2 ARBs have been shown to retard the progression of albuminuria and the development and progression of nephropathy, 4 but there are few data of the ARBs action on metabolic parameters, especially in comparison with ACE inhibitors, in diabetic subjects.…”
mentioning
confidence: 99%
“…In cases of mildto-moderate hypertension, monotherapy controls BP in 40% to 50% of patients. This level of efficacy is similar to those of angiotensin-converting enzyme (ACE) inhibitors, diuretics, calcium antagonists and β -blocking agents ( 4 ). AT 1 receptor blockers are particularly indicated for patients with hypertension who are being treated with ACE inhibitors and have developed side effects, such as cough or angioedema ( 5 ).…”
Section: Introductionmentioning
confidence: 79%
“…Similarly, it has recently been demonstrated that the progression of renal injury in diabetic nephropathy is prevented by the inhibition of ANG II activity by ARBs (5,6,18). Although these observations clearly indicate the renal protective action of ARBs, there exists some heterogeneity in their antagonistic activity on AT1 receptors (7,9,19,20). Furthermore, it has been demonstrated ARBs, like ACE-Is, enhance the production of NO via AT1 receptor blockade (10,21).…”
Section: Discussionmentioning
confidence: 97%